2011
DOI: 10.1063/1.3624778
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lower hybrid wave coupling and current drive experiments at different configurations in experimental advanced superconducting tokamak

Abstract: Using a 2 MW 2.45 GHz lower hybrid wave (LHW) system installed in experimental advanced superconducting tokamak, we have systematically carried out LHW-plasma coupling and lower hybrid current drive experiments in both divertor (double null and lower single null) and limiter plasma configuration with plasma current (I p ) $ 250 kA and central line averaged density (n e ) $ 1.0-1.3 Â 10 19 m À3 recently. Results show that the reflection coefficient (RC) first is flat up to some distance between plasma and LHW g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…28 The H-mode discharges were achieved by LHW, 29 ICRF, 30 or their combination. The energy confinement of these RF heated H-modes has been studied.…”
Section: Experimental Setup On Eastmentioning
confidence: 99%
“…28 The H-mode discharges were achieved by LHW, 29 ICRF, 30 or their combination. The energy confinement of these RF heated H-modes has been studied.…”
Section: Experimental Setup On Eastmentioning
confidence: 99%
“…For the present LHW system on EAST of 2 MW/2.45 GHz, it consists of 20 main multijunction waveguides arranged in an array of five rows and four columns. 9 The n k spectrum radiated from the launcher is usually centered at 2.1 but can be varied between 1.85 and 2.58 by varying the phase difference between adjacent main waveguides from À90 to 180 . Thus, we perform the calculation with many rays and each ray has a definite initial n k and launched power that according to Brambilla's treatment with n peak k ¼ 2:1, as shown in Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…6 On Experimental Advanced Superconductor Tokamak (EAST), LHCD has been used to achieve a long-pulse Hmode discharge to provide an intrinsic boundary control for edge localized modes. 8,9 If the accessibility condition is satisfied, the coupled lower hybrid wave from an external antenna can propagate into core region with high plasma density and temperature. As the wave phase velocity becomes comparable with the electron thermal velocity, the LHW can interact with electrons at high velocities around three times the electron thermal velocity via Landau damping.…”
Section: Introductionmentioning
confidence: 99%
“…To improve LHW-plasma coupling, local gas puffing near the antenna has been developed, which has been studied in JT-60U, ASDEX, JET, Tore-supra, HT-7 Ikeda et al 1994;Pericoli-Ridolfini et al 2004;Ekedahl et al 2005Ekedahl et al , 2009Ekedahl et al , 2012Ding et al 2010). Also, in EAST, with the 2.45 GHz LHCD system, local gas puffing from the electron drift side (GIM_e) and ion drift side Studies of challenge in LHCD capability at high density regime in EAST 3 FIGURE 2.…”
Section: Issue Of Lhw-plasma Couplingmentioning
confidence: 99%
“…In order to obtain the scientific goal of EAST (a long pulse and high performance), two LHCD systems have been developed and exploited on EAST, operating, respectively, at 2.45 GHz (4 MW) (Ding et al 2011 and 4.6 GHz (6 MW) (Ding et al 2013a,b). Typical spectra calculated by an advanced lower hybrid antenna (ALOHA) (Hillairet et al 2010) are shown in figure 1, in which N // is the refractive index in the parallel direction, N peak // is the corresponding peak value and Φ refers to the phase difference between the adjacent main waveguides.…”
Section: Introductionmentioning
confidence: 99%